Endangering the natural basis of life is unjust: on the status and future of the sustainability discourse - Becker, Christian; Ewringmann, Dieter; Faber, Malte; Petersen, Thomas; Zahrnt, Angelika (Ethics, policy and environment, 2015)
The paper critically examines the status of the sustainability discourse and sustainability politics against the backdrop of considerations about the meaning of justice in the context of sustainability. We argue that the preservation of the natural basis of life is by itself a requirement of justice. However, the crucial role of the ecological dimension of sustainability has been neglected due to a problematic interpretation of the economic dimension, a limited understanding of justice, and an overemphasis of economic growth and growth politics. We propose to reposition the sustainability discourse and sustainability politics by prioritizing the long-term protection of the natural basis of life as the essential foundation of future development, welfare, and justice.
Gesehen am 03.08.2020